2009
DOI: 10.2174/1876214x00902010086
|View full text |Cite
|
Sign up to set email alerts
|

Cataluminescence and Catalysis Properties of CO Oxidation Over Porous Network of ZrO2 Nanorods Synthesized by a Bio-Template

Abstract: A network of ZrO 2 nanorods was prepared using the porous biomembranes as templates. The sample was characterized by SEM, XRD and nitrogen physicosorption isotherm. ZrO 2 nanoparticles were also prepared with a hydrothermal method in order to compare with this network. The results showed that after being calcined at 800 o C for 24 h, a volume contraction of ZrO 2 nanorod network occurred accompanied by a phase transformation of tetragonal-to-monoclinic ZrO 2 ; but the nanoparticles have grown into the large mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Teng et al . also investigated CTL properties of CO oxidation over ZrO 2 samples and found that the calcined network showed a higher CTL intensity than the calcined particles. They pointed out that the reason was the high surface area and advanced pores of the former.…”
Section: Instruments and Materialsmentioning
confidence: 99%
“…Teng et al . also investigated CTL properties of CO oxidation over ZrO 2 samples and found that the calcined network showed a higher CTL intensity than the calcined particles. They pointed out that the reason was the high surface area and advanced pores of the former.…”
Section: Instruments and Materialsmentioning
confidence: 99%